Chiara Maria Mauro, Archaic and Classical Harbours of the Greek World. The Aegean and Eastern Ionian contexts, Oxford, Archaeopress Publishing LTD, 2019, 115 pp. [ISBN: 978-1-78969-128.3]. - Tomei, Francesca (Gerión. Revista de Historia Antigua, 2020)
Reseña del libro de Chiara Maria Mauro, Archaic and Classical Harbours of the Greek World. The Aegean and Eastern Ionian contexts, Oxford, Archaeopress Publishing LTD, 2019, 115 pp. [ISBN: 978-1-78969-128.3].